Effect of Cataract Opacity Type and Glaucoma Severity on Visual Field Index. Issue 6 (June 2016) - Chung, Hye Jin; Choi, Jeong Hoon; Lee, Young-Chun; Kim, Su-Young
ABSTRACT: Purpose: To determine the effect of cataract opacity type and glaucoma severity on the visual field index (VFI). Methods: A total of 152 eyes of 152 patients were analyzed. Patients with glaucoma, previous evaluation with the Swedish Interactive Threshold Algorithm-standard 24-2 VFs, visually significant cataracts, and VFs before surgery were included in this study. Cataract opacity was classified as cortical, nuclear sclerotic, or posterior subcapsular. The patients underwent phacoemulsification cataract extraction surgery. A postoperative VF test was done within 10 months of the previous VF. Glaucoma severity was classified by the postoperative mean deviation (MD) value. Changes in MD, pattern standard deviation (PSD), and VFI value before and after surgery were compared according to cataract opacity and glaucoma severity. Results: The mean age at cataract surgery was 72 ± 10 years. The MD, PSD, and VFI values were less influenced by nuclear sclerotic cataract opacity. In patients with early glaucoma (MD > −6), particularly with cortical cataract opacity, MD, PSD, and VFI improved after cataract extraction (p < 0.05). Cataract opacity could make interpreting the VF indices more difficult in patients with early glaucoma. VFI was a reliable index that was less affected by cataract extraction, except in patients with early glaucoma (MD > −6) and cortical cataract opacity. Conclusions: Existing cataract opacity and the type of cataract opacity may affect the VF test results. Therefore, both glaucoma severity and the type of cataract opacity should be considered when interpreting VF results.